Parsing a plethora of pollen: the role of pollen size and shape in the evolution of Boraginaceae. (17th August 2021) - Noroozi, Maryam; Ghahremaninejad, Farrokh; Bogler, David; Witherspoon, Jocelyn M.; Ryan, Gillian L.; Miller, James S.; Riahi, Mehrshid; Cohen, James I.
Abstract: Pollen, the microgametophyte of seed plants, has an important role in plant reproduction and, therefore, evolution. Pollen is variable in, for example, size, shape, aperture number; these features are particularly diverse in some plant taxa and can be diagnostic. In one family, Boraginaceae, the range of pollen diversity suggests the potential utility of this family as a model for integrative studies of pollen development, evolution and molecular biology. In the present study, a comprehensive survey of the diversity and evolution of pollen from 538 species belonging to 72 genera was made using data from the literature and additional scanning electron microscopy examination. Shifts in diversification rates and the evolution of various quantitative characters were detected, and the results revealed remarkable differences in size, shape and number of apertures. The pollen of one subfamily, Boraginoideae, is larger than that in Cynoglossoideae. The diversity of pollen shapes and aperture numbers in one tribe, Lithospermeae, is greater than that in the other tribes. Ancestral pollen for the family was resolved as small, prolate grains that bear three apertures and are iso‐aperturate. Of all the tribes, the greatest number of changes in pollen size and aperture number were observed in Lithospermeae and Boragineae, and the number of apertures was found to be stable throughout all tribes of Cynoglossoideae. In addition, the present study showed that diversification of Boraginaceae cannot be assigned to a single factor, such as pollen size, and the increased rate of diversification for species‐rich groups (e.g. Cynoglossum ) is not correlated with pollen size or shape evolution. The palynological data and patterns of character evolution presented in the study provide better resolution of the roles of geographical and ecological factors in the diversity and evolution of pollen grains of Boraginaceae, and provide suggestions for future palynological research across the family.